Assessment of women’s awareness about reproductive and breast cancers - Kosińska, Karina Weronika; Lubawa, Weronika Maria; Szczęśniak, Magdalena; Plagens-Rotman, Katarzyna; Miechowicz, Izabella; Bączyk, Grażyna; Ulatowska, Agnieszka; Umbreit, Michał (Journal of Medical Science, 2017)
Introduction. The aspect of prevention and treatment of malignant tumours is a key problem of public health in Poland, posing a great challenge for the health care system. A perfect method of fighting against neoplasms is prevention. Its widespread use may allow reduction in the risk of developing cervical and breast cancer. Aim. The aim of the paper was to assess women’s awareness about prophylaxis and risk factors related to the development of reproductive and breast cancers among women subject to the survey. Materials and Methods. The analysis comprised a group of 154 women at the age from 17 to 70. The study was conducted between 17 March and 30 July 2015. The research tool used in the study was an independently prepared survey questionnaire. Results. The biggest group of respondents (48.70%) was made up of women at the age from 20 to 30. 68.83% of the women had a secondary level education, 42.20% were women from cities of between 51.000 to 100.000 inhabitants and only 1.94% represented large cities of over 500.000 inhabitants. A change in the size or shape of the breast (88.96%) and changes in the look of the nipple (86.36%) were quoted as the most frequent symptom of breast cancer. Conclusions. The knowledge about reproductive organs and breast cancer prevention among women is not fully satisfactory and needs to be broadened. Media (internet, television) were the most popular source of information on cancer prevention among the respondents. It is necessary for family doctors and midwives to intensify health-care activities aimed especially at women who are the age associated with an increased risk for cancer.